Performance Evaluation of Drainage Systems in Waterlogged Coastal Sandy Clay Loam Soil at a Pilot Area in Krishna Western Delta - Srinivasulu, A; Satyanaryana, T V; Babu, M Raghu; Kumar, H.V Hema (Journal of Agricultural Engineering, 2006)
Pipe and open subsurface drainage systems were installed in an area of 12 ha in farmers’ fields at Uppugunduru pilot area in Krishna Western Delta (KWD) in South India to combat the problems of water logging (depth of water table, 0 to 2.04 m) and salinity (ECe, 1.0 to 52.7 dS m?Â¹; pH, 6.5 to 8.8). Ten pipe drains were laid at three different spacing of 30,45 (design) and 60 m using two types of synthetic envelope materials, namely nylon mesh and geo-textile. Six open drains were laid at 50 m spacing. Monitoring of the performance of drainage systems for a period of 3 years from 1999-00 to 2001-02 indicated that the average discharge from the pipe drains laid at 30 m spacing was the highest in all the years when compared to the pipe drains laid at 45 and 60 m spacing. As the spacing increased, the drain discharge decreased. However, no definite trend was observed with regard to the effect of envelope material on drain discharge. The water table, which used to be very close to the ground surface during the main crop period from October to January, could be lowered by 0.25 to O.4m below the ground surface because of drainage systems. A total of 765.13 tons of salts were disposed through the drainage systems during the period of three years.